Production Process of Fiberglass Fast Interceptor Boat in Malaysia - Yaacob, Amirrudin; Zakaria, Zainul Azhar; Zarina, M.K Puteri; Koto, Jaswar; Kidd, Peter (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
The conventional fiberglass boatbuilding is still widely practiced in Malaysia compared to the modern fiberglass boatbuilding. Every fiberglass boat builder has different methods or processes for the construction of fiberglass boats. The production process and procedure of conventional fiberglass boatbuilding is far from the influence of advance technology. This study presents the production process for modern fiberglass boatbuilding in Malaysia which uses Resin Infusion Method as the latest method in composite technology and applied on Fiberglass Fast Interceptor Boat. The study was conducted in UES International Sdn Bhd in Malacca, Malaysia.